Energy Markets and Economics Ⅱ - Narayan, Seema (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This issue brings together a collection of papers that provide economic insights into the modern energy market, which is still dominated by crude oil but has expanded to incorporate new energy sources in the form of coal, natural gas, and a mixture of renewable energy sources. Given the differences in the dynamics at play with different energy sources, particularly in relation to price determination, the impact they have on the environment, their importance in the energy mix and energy policy, and so forth, it has become imperative to check their behavior using economic models. Papers 1-3 provide some perspective on oil price determination by focusing on the time-varying nature of supply shocks linked to oil producers (Paper 1), OPEC's announcements (2), and the heterogeneous interconnections of supply or demand shocks over time horizons and different countries (3). Papers 4-6 compare different energy sources within the energy market and other markets (4); explore the importance of energy storage in the electricity market (5); and examine the dynamic relationship between prices of substitutes (oil price) on the natural gas market in China (6). The final four studies examine the impact of renewable and nonrenewable energy on the macroeconomy and the environment.